Synopsis of terrestrial isopods (Crustacea: Isopoda: Oniscidea) from Brazilian caves, with emphasis on new records from north, midwest, northeast and southeast regions. Issue 17 (11th May 2019) - Fernandes, Camile Sorbo; Campos-Filho, Ivanklin Soares; Beatriz Araujo, Paula; Bichuette, Maria Elina
ABSTRACT: Terrestrial isopods are one of the most diverse groups in the subterranean environment. To date, 39 oniscidean species are known from Brazilian caves; however, this number falls far short of the real diversity of the group, because even in the best studied areas new records are still frequent. During the last years many surveys in several caves from the states of Bahia, Minas Gerais, Goiás and Pará have been conducted. These efforts resulted in a representative scientific collection with great diversity of oniscideans. Here we addressed the current state of knowledge of oniscidean fauna from Brazilian caves compiling the described species and adding new records of our own surveys. We present a list of 24 new records of terrestrial isopods from 53 caves, with brief comments about the presence of troglomorphic character states and known distribution, in- and outside of caves. Also, we addressed the need of validation of new species and of additional efforts to assign a conservation category to each one, which is the key step to the preservation of the subterranean environment and its biodiversity. Any delay may yield permanent loss of biodiversity of these localities, considering the several conservation concerns the Brazilian caves have been facing. http://www.zoobank.org/urn:lsid:zoobank.org:pub:5883EF8A-7CFF-4C98-A5FA-1B06ABEE23D8